Prevalence of Coxiella burnetii and Brucella spp. in tissues from subsistence harvested northern fur seals (Callorhinus ursinus) of St. Paul Island, Alaska - Duncan, Colleen (BioMed Central, 2014)
BACKGROUND: The northern fur seal (Callorhinus ursinus) is an important cultural and nutritional resource for the Aleut community on St. Paul Island Alaska. In recent years, an increasing number of zoonotic pathogens have been identified in the population, but the public health significance of these findings is unknown. To determine the prevalence of Coxiella burnetii and Brucella spp. in northern fur seal tissues, eight tissue types from 50 subsistence-harvested fur seals were tested for bacterial DNA by real-time polymerase chain reaction. FINDINGS: Of the 400 samples tested, only a single splenic sample was positive for Brucella spp. and the cycle threshold (ct) value was extremely high suggesting a low concentration of DNA within the tissue. C. burnetii DNA was not detected. CONCLUSIONS: Findings suggest that the risk of humans contracting brucellosis or Q fever from the consumption of harvested northern fur seals is low.